Use of a Non-Pharmacological Pain Relief Kit to Reduce Opioid Use Following Orthopedic Surgery: A Prospective Randomized Study - Denis J O'Hara; Timothy F Tyler; Malachy P McHugh; Susan Y Kwiecien; Tyler Bergeron (North American Sports Medicine Institute, 2022)
# Introduction Opioid prescription to treat pain among orthopedic surgery patients remains common practice in the United States but overprescribing opioids can lead to abuse. The purpose of this study was to determine the effect of a multimodal non-pharmacological 'pain relief kit' on pain, function, and opioid consumption in individuals recovering from orthopedic surgery. # Hypothesis Patients provided with the pain relief kit would consume less opioid medication, report lower pain levels, and have better functional outcome scores than the control group. # Level of Evidence 2b # Methods Fifty-three subjects (18 women, 35 men) having orthopedic surgery were randomly assigned to either receive the Pain Relief Kit (treatment) or control group. At the first postoperative physical therapy visit (within 1 week of surgery) the treatment group was provided elastic resistance bands, kinesiology tape, Biofreeze, and a hot/cold pack as part of the Pain Relief Kit. Patients completed the SF-36 and either the DASH or LEFS questionnaires consistent with their surgery at baseline and four weeks post-op. Both groups reported daily pain (Visual Analogue Scale), opioid use, and over the counter medication use. The treatment group also recorded daily kit modality use. # Results There was no significant difference in total opioid use between the treatment (108±252 milligram morphine equivalents) and control groups (132±158 MME; p=0.696). Opioid use and pain declined from week one to four with no difference between groups (p<0.001). Outcome scores and SF-36 scores improved from week one to four with no difference between groups (p<0.001). # Conclusion A non-pharmacological pain relief kit did not have an effect on opioid use in this patient population nor did it improve pain relief or function compared to controls.